AGRONOMIC CHARACTERISTICS OF CORN SUBMITTED TO SOURCES AND INSTALLMENT OF NITROGEN IN COVERAGE - Portela, M. G. T.; Araújo, R. L.; Barbosa, R. P.; da Rocha, D. R. (Revista Brasileira de Engenharia de Biossistemas, 2016)
The objective of this study was to evaluate the agronomic characteristic of corn (Zea mays L.) submitted to six levels of nitrogen fertilization installment. The experiment was conduct in the experimental area of the College of Technical Teresina, located in Teresina -PI, using a design in randomized blocks in factorial design, with the treatments six types of splitting of N applied in coverage(without application, application 1, 2 applications 3 applications, 4 applications and 5 applications), using two types of nitrogen fertilizers (ammonium sulfate and urea). The sowing wascarryout with the cultivar BM 3061 and were assessthe following plant parameters: number, productivity, diameter, length of green ears, plant height and height insertionof the first ear.In all variables except height of the first ear insertion, ammonium sulfate promoted better results than urea. Evaluating the division of ammonium sulfate, it did not affect the diameter and length of spikes. However, from 3 topdressing fertilizer this, it is possible to better promote green corn yield in the region.